Strategies For Building Peace in Multicultural Society in The Digital Era: New Challenges and Inclusive Approaches - Situmorang, May Laura Thecci; Sagala, Parluhutan; Triadi, Irwan; Setiawibawa, Rachmat; Uksan, Arifuddin (International Journal of Education, Vocational and Social Science, 2026)
The digital era has changed the dynamics of social interaction, including in multicultural societies, by expanding communication spaces while simultaneously presenting new challenges in the form of polarization, the spread of hoaxes, and cultural stereotypes. This article aims to analyze peacebuilding strategies in multicultural societies in the digital era through an inclusive approach that emphasizes digital literacy, legal awareness, and ethical online interactions. The research method used is qualitative, with a desk study approach and normative analysis of academic literature, regulations, and best practices in maintaining social harmony. The analysis results indicate that an effective strategy requires a combination of formal and non-formal education to improve digital literacy, ongoing public campaigns to build social and legal awareness, and multi-stakeholder collaboration between the government, educational institutions, civil society organizations, and technology platforms. This inclusive approach is expected to not only strengthen individuals' capacity to respond to the dynamics of cyberspace but also create a safe, harmonious digital space that supports the strengthening of humanitarian values ​​and social cohesion in multicultural societies. These findings contribute to academic thinking on digital-based peacebuilding and adaptive strategies in the context of cultural plurality.